2018
DOI: 10.1007/s12070-018-1466-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Therapy with Corticosteroids in Nasal Polyposis: A Bone Metabolism Assessment

Abstract: Chronic rhinosinusitis associated with nasal polyposis (RSCwNP) affects 4% of the general population. As chronic condition, it requires chronic pharmacological treatment, whereas the surgical approach becomes necessary in obstructive and/or complicated cases. Intranasal and systemic corticosteroids (CS) represent the ''Gold Standard'' treatment for RSCwNP. The present study aimed to evaluate the side effects of prednisone in a group of patients with RSCwNP treated with long-term CS. In particular, attention wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(33 reference statements)
0
1
1
Order By: Relevance
“…They only speculated the occurrence of osteoporosis as with other chronic inflammatory conditions. Contrasting results from the study by Gelardi et al that assessing bone metabolism in chronic rhinosinusitis associated with nasal poliposis and long-term therapy with corticosteroids, showed that the likelihood of osteoporosis or osteopenia between affected and healthy subjects was superimposable with no statistically significant parameter predicting alterations of bone metabolism [66].…”
Section: Pollen-allergycontrasting
confidence: 59%
“…They only speculated the occurrence of osteoporosis as with other chronic inflammatory conditions. Contrasting results from the study by Gelardi et al that assessing bone metabolism in chronic rhinosinusitis associated with nasal poliposis and long-term therapy with corticosteroids, showed that the likelihood of osteoporosis or osteopenia between affected and healthy subjects was superimposable with no statistically significant parameter predicting alterations of bone metabolism [66].…”
Section: Pollen-allergycontrasting
confidence: 59%
“…It was reported by Ostergaard and colleagues in a study that included 1,362 patients that a single injection of corticosteroids have no complications and supported no concern for adrenal suppression, osteoporosis, or serious tissue atrophy [ 77 ]. Other authors have foreseen the actual safety of systemic corticosteroids without the reported side effects [ 43 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%